Application of artificial intelligence in NFV - Zengyi LIU; Bo LEI; Mingchuan YANG (Dianxin kexue)
How to deal with the complicated management problem after network function virtualization,how to flexibly schedule the network,all these problems need to be solved in order to develop the NFV.The rise of artificial intelligence provides a new solution for the management and orchestration in the NFV system.The present situations of NFV and artificial intelligence were summarily introduced,and use-cases of artificial intelligence in NFV were discussed.In addition,a solution for the management of VNF lifecycle management based on machine learning was proposed to provide reference for artificial intelligence technology in the application of NFV.